SISTEM INFORMASI GEOGRAFIS BERBASIS WEB UNTUK INFORMASI PENDIDIKAN, DI KOTA PALANGKARAYA DENGAN MENGGUNAKAN GOOGLE MAP API (Universitas Palangka Raya, 2016)
Along with the development of technology in the world of informatics and the position of Palangkaraya As provincial capital of Central Kalimantan, of course, the broader region than in other districts that make community difficulty remembering or knowing the location of existing educational institutions in the city of Palangkaraya. The difficulty of the public to obtain information about the educational institutions, especially those in Palangkaraya. It makes people Palangkaraya or arrivals outside the area who want to know the information in the educational institutions of Palangkaraya trouble. Based on the background that have been outlined. The author formulates the problem of how to design and create applications Location Based Service (LBS) Mobile Web-Based Education Institutions.This study aims to create a system Applications Location Based Service (LBS) Mobile Web-Based Educational Institutions that can provide location-based services to the public in obtaining information about the location and the educational institutions, both formal and non-formal located in Palangkaraya. The benefit to help people find the location of the institution.The result of this study is an application of Location Based Service (LBS) Institutions of Palangkaraya that can display maps and map these educational institutions educational institutions perkategori in Palangkaraya with a browser supporting HTML 5 format and can be beneficial to society.